Memória, cultura e linguagem da comunidade quilombola do ramal do Piratuba, Abaetetuba-PA - COSTA, Rita Oliveira (2021)
The language currently spoken in Brazil is the result of the gigantic process of transformationthat the country has undergone over the years. It has a rich vocabulary with several words of indigenous, African and European descent. There is no precise date for the formation of quilombola communities, theoretically these mocambos were formed by slaves who fled their masters. The first indicative signs of the presence of African descent in Abaetetuba were observed by the parish priests of the municipality, who carefully examined the communities that had Creole characteristics. Just as in the age of beauty standards we are pressured to follow such prototypes, so in language we become hostages, as there is a strong demand for pronouncing a formal language. It is known that language is a precondition established by the community for the construction of culture. So, why is the mother tongue of the quilombola community of Ramal do Piratuba not passed on through the generations if we know that language is a cultural manifestation? The research was conducted in the quilombola community of Ramal do Piratuba, located in the municipality of Abaetetuba, State of Pará. The aim of this study is to rescue the linguistic culture in memory, to allow future generations to have access to this knowledge. The result is the rescue of memory, explored through culture and language, thus allowing future generations to relate to the historicity of their people.